2000
DOI: 10.1038/sj.ejhg.5200403
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular advances in autosomal dominant cerebellar ataxias: from genotype to phenotype and physiopathology

Abstract: Major advances have been made in the understanding of autosomal dominant cerebellar ataxias since genetic markers came into use in the 1980s. The subsequent mapping of nine genes, six of which have been identified, involved in this clinically diverse group of disorders highlighted their great genetic heterogeneity. Evidence is now accumulating that, except for SCA8, the same molecular and physiopathological processes underlie these diseases and other neurodegenerative disorders sharing the same mutational basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
108
0
9

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(121 citation statements)
references
References 153 publications
(156 reference statements)
4
108
0
9
Order By: Relevance
“…A ataxia é caracterizada por um desequilíbrio ao caminhar e é um dos principais sintomas da Doença de Machado-Joseph (DMJ) 1 . A DMJ pertence ao grupo das ataxias espinocerebelosas autossômicas dominantes 2 , deve-se à presença de mutação genética constituída de repetições trinucleotídicas instáveis (CAG) que aloca-se no cromossomo 14 3 .…”
Section: Introductionunclassified
“…A ataxia é caracterizada por um desequilíbrio ao caminhar e é um dos principais sintomas da Doença de Machado-Joseph (DMJ) 1 . A DMJ pertence ao grupo das ataxias espinocerebelosas autossômicas dominantes 2 , deve-se à presença de mutação genética constituída de repetições trinucleotídicas instáveis (CAG) que aloca-se no cromossomo 14 3 .…”
Section: Introductionunclassified
“…Some studies have established that the anticipation is typically high for spinocerebellar ataxis and MachoadoJoseph disease [13]. Since the length of the CAG repeats in a gene may increase as they are transmitted to the next generation [13], genetic instability of trinucleotide repeats contributes to anticipation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the length of the CAG repeats in a gene may increase as they are transmitted to the next generation [13], genetic instability of trinucleotide repeats contributes to anticipation. For instance, CAG repeats in SCA1 tend to lengthen during spermatogenesis, explaining why the severity of the disease frequently increases from one generation to the next [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the SCA type 7, the cerebellar ataxia is associated with progressive visual loss that results from the retina degeneration (progressive macular degeneration). Pyramidal signs, ophthalmoplegia, Parkinsonism, slow saccades and weakness (3)(4)(5) can also be associated with it. Studies (4,5) have identified the occurrence of olivopontocerebellar degeneration associated with the reduction of retinal ganglion cells and pigmentary macular dystrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Pyramidal signs, ophthalmoplegia, Parkinsonism, slow saccades and weakness (3)(4)(5) can also be associated with it. Studies (4,5) have identified the occurrence of olivopontocerebellar degeneration associated with the reduction of retinal ganglion cells and pigmentary macular dystrophy. The clinical condition may develop during childhood until the 60 years of age, and the younger the individual affected, the faster the disease progresses (5) .…”
Section: Introductionmentioning
confidence: 99%